Nuclear import of glucokinase in pancreatic beta-cells is mediated by a nuclear localization signal and modulated by SUMOylation. (15th October 2017) - Johansson, Bente Berg; Fjeld, Karianne; Solheim, Marie Holm; Shirakawa, Jun; Zhang, Enming; Keindl, Magdalena; Hu, Jiang; Lindqvist, Andreas; Døskeland, Anne; Mellgren, Gunnar; Flatmark, Torgeir; Njølstad, Pål Rasmus; et al.
Abstract: The localization of glucokinase in pancreatic beta-cell nuclei is a controversial issue. Although previous reports suggest such a localization, the mechanism for its import has so far not been identified. Using immunofluorescence, subcellular fractionation and mass spectrometry, we present evidence in support of glucokinase localization in beta-cell nuclei of human and mouse pancreatic sections, as well as in human and mouse isolated islets, and murine MIN6 cells. We have identified a conserved, seven-residue nuclear localization signal ( 30 LKKVMRR 36 ) in the human enzyme. Substituting the residues KK 31, 32 and RR 35, 36 with AA led to a loss of its nuclear localization in transfected cells. Furthermore, our data indicates that SUMOylation of glucokinase modulates its nuclear import, while high glucose concentrations do not significantly alter the enzyme nuclear/cytosolic ratio. Thus, for the first time, we provide data in support of a nuclear import of glucokinase mediated by a redundant mechanism, involving a nuclear localization signal, and which is modulated by its SUMOylation. These findings add new knowledge to the functional role of glucokinase in the pancreatic beta-cell. Highlights: Glucokinase is present in the nucleus of human beta-cell islets. Glucokinase contains a functional nuclear localization signal. SUMOylation of glucokinase modulates its nuclear import. High glucose does not affect the nuclear/cytosolic glucokinase ratio.